Pseudomonas aeruginosa elastase does not inactivate alpha 1-proteinase inhibitor in the presence of leukocyte elastase. - Padrines, M (1989)
Pseudomonas aeruginosa elastase rapidly inactivates alpha 1-proteinase inhibitor by splitting its Pro-357-Met-358 peptide bond. The present study was aimed at testing whether this reaction takes place in the presence of leukocyte elastase. To this end was added alpha 1-proteinase inhibitor to a mixture of the two elastases, and we performed the following assays: (i) measurement of the residual leukocyte elastase activity, (ii) sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and (iii) immunoassay of the leukocyte elastase-alpha 1-proteinase inhibitor complex. These experiments were done with various concentrations of the three proteins. All experiments gave the same result: leukocyte elastase was fully inhibited by alpha 1-proteinase inhibitor in the presence of P. aeruginosa elastase even when the bacterial enzyme was 10-fold more concentrated than the neutrophil enzyme. We also measured the initial rate of the P. aeruginosa elastase-catalyzed inactivation of alpha 1-proteinase inhibitor as a function of the inhibitor concentration. The kcat/Km value derived from this experiment was 9 x 10(4) M-1 s-1, a value much lower than the rate constant for the leukocyte elastase-inhibitor association (kass, 1.7 x 10(7) M-1 s-1). This rationalizes the above results. In conclusion, when alpha 1-proteinase inhibitor is faced with its target enzyme, leukocyte elastase, it will perform its physiologic antielastase function even if the bacterial elastase is present in excess.